Extensive and Persistent Dermal Melanocytosis in a Male Carrier of Mucopolysaccharidosis Type IIIC (Sanfilippo Syndrome): A Case Report - Maurizio Romagnuolo; Chiara Moltrasio; Serena Gasperini; Angelo Valerio Marzano; Stefano Cambiaghi (MDPI AG, 2023)
Congenital dermal melanocytosis (DM) represents a common birthmark mainly found in children of Asian and darker skin phototype descent, clinically characterized by an oval blue-grey macule or macules, commonly located on the lumbosacral area. In rare DM cases, when presenting with diffuse macules persisting during the first years of life, it could represent a cutaneous feature of mucopolysaccharidoses (MPS). Extensive congenital DM is actually associated with Hurler syndrome (MPS type I) and Hunter syndrome (MPS type II), although several reports also described this association with MPS type VI and other lysosomal storage disorders (LySD), including GM1 gangliosidosis, mucolipidosis, Sandhoff disease, and Niemann-Pick disease. Here, we present the case of a two-year-old boy presenting with extensive dermal melanocytosis, generalized hypertrichosis, and chronic itch, harboring a heterozygous variant of uncertain significance, NM_152419.3: c.493C>T (p.Pro165Ser), in the exon 4 of HGSNAT gene, whose mutations are classically associated with MPS IIIC, also known as Sanfilippo syndrome. This is the first report that highlights the association between extensive congenital DM and MPS type IIIC, as well as a pathogenetic link between heterozygous LySD carrier status and congenital DM. We speculate that some cases of extensive congenital DM could be related to heterozygous LySD carriers, as a manifestation of a mild clinical phenotype.